Targeted hypothermia versus targeted normothermia after out-of-hospital cardiac arrest: a statistical analysis plan - Jakobsen, Janus Christian; Dankiewicz, Josef; Lange, Theis; Cronberg, Tobias; Lilja, Gisela; Levin, Helena; Bělohlávek, Jan; Callaway, Clifton; Cariou, Alain; Erlinge, David; Hovdenes, Jan; Joannidis, Michael; et al. (Trials, 2020)
BACKGROUND: To date, targeted temperature management (TTM) is the only neuroprotective intervention after resuscitation from cardiac arrest that is recommended by guidelines. The evidence on the effects of TTM is unclear. METHODS/DESIGN: The Targeted Hypothermia Versus Targeted Normothermia After Out-of-hospital Cardiac Arrest (TTM2) trial is an international, multicentre, parallel group, investigator-initiated, randomised, superiority trial in which TTM with a target temperature of 33 °C after cardiac arrest will be compared with a strategy to maintain normothermia and active treatment of fever (≥ 37.8 °C). Prognosticators, outcome assessors, the steering group, the trial coordinating team, and trial statisticians will be blinded to treatment allocation. The primary outcome will be all-cause mortality at 180 days after randomisation. We estimate a 55% mortality in the targeted normothermia group. To detect an absolute risk reduction of 7.5% with an alpha of 0.05 and 90% power, 1900 participants will be enrolled. The secondary neurological outcome will be poor functional outcome (modified Rankin scale 4-6) at 180 days after cardiac arrest. In this paper, a detailed statistical analysis plan is presented, including a comprehensive description of the statistical analyses, handling of missing data, and assessments of underlying statistical assumptions. Final analyses will be conducted independently by two qualified statisticians following the present plan. DISCUSSION: This SAP, which was prepared before completion of enrolment, should increase the validity of the TTM trial by mitigation of analysis-bias.
Keywords: horečka; terapeutická hypotermie; hypotermie; Humans; Fever; Hypothermia, Induced; tělesná teplota; výsledek terapie; Hypothermia; Cardiopulmonary Resuscitation; Out-of-Hospital Cardiac Arrest; lidé; kardiopulmonální resuscitace; Treatment Outcome; Body Temperature; zástava srdce mimo nemocnici